Pathogenesis, immunology, and immune‐targeted management of the multisystem inflammatory syndrome in children (MIS‐C) or pediatric inflammatory multisystem syndrome (PIMS): EAACI Position Paper. Issue 1 (4th January 2023) - Feleszko, Wojciech; Okarska‐Napierała, Magdalena; Buddingh, Emilie Pauline; Bloomfield, Marketa; Sediva, Anna; Bautista‐Rodriguez, Carles; Brough, Helen A.; Eigenmann, Philippe A.; Eiwegger, Thomas; Eljaszewicz, Andrzej; Eyerich, Stefanie; Gomez‐Casado, Cristina; et al.
Abstract: Multisystem inflammatory syndrome in children (MIS‐C) is a rare, but severe complication of coronavirus disease 2019 (COVID‐19). It develops approximately 4 weeks after severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) infection and involves hyperinflammation with multisystem injury, commonly progressing to shock. The exact pathomechanism of MIS‐C is not known, but immunological dysregulation leading to cytokine storm plays a central role. In response to the emergence of MIS‐C, the European Academy of Allergy and Clinical Immunology (EAACI) established a task force (TF) within the Immunology Section in May 2021. With the use of an online Delphi process, TF formulated clinical statements regarding immunological background of MIS‐C, diagnosis, treatment, follow‐up, and the role of COVID‐19 vaccinations. MIS‐C case definition is broad, and diagnosis is made based on clinical presentation. The immunological mechanism leading to MIS‐C is unclear and depends on activating multiple pathways leading to hyperinflammation. Current management of MIS‐C relies on supportive care in combination with immunosuppressive and/or immunomodulatory agents. The most frequently used agents are systemic steroids and intravenous immunoglobulin. Despite good overall short‐term outcome, MIS‐C patients should be followed‐up at regular intervals after discharge, focusing on cardiac disease, organ damage, and inflammatory activity. COVID‐19 vaccination is a safe and effective measure to prevent MIS‐C. In anticipation of further research, we propose a convenient and clinically practical algorithm for managing MIS‐C developed by the Immunology Section of the EAACI.